Pan-mutant-IDH1 inhibitor BAY1436032 is highly effective against human IDH1 mutant acute myeloid leukemia in vivo - Chaturvedi, Anuhar; Pusch, Stefan; Stichel, Damian; Bochtler, Tilmann; Ho, Anthony Dick; Deimling, Andreas von; Rippe, Karsten; Krämer, Alwin (Leukemia, 2017)
Neomorphic mutations in isocitrate dehydrogenase 1 (IDH1) are frequently found in several human cancer types including acute myeloid leukemia (AML) and lead to the production of high levels of the oncometabolite (R)-2-hydroxyglutarate (R-2HG). Here we report the characterization of BAY1436032, a novel pan-mutant IDH1 inhibitor, both in vitro and in vivo. BAY1436032 specifically inhibits R-2HG production and colony growth, and induces myeloid differentiation of AML cells carrying IDH1R132H, IDH1R132C, IDH1R132G, IDH1R132L and IDH1R132S mutations. In addition, the compound impacts on DNA methylation and attenuates histone hypermethylation. Oral administration of BAY1436032 led to leukemic blast clearance, myeloid differentiation, depletion of leukemic stem cells and prolonged survival in two independent patient-derived xenograft IDH1 mutant AML mouse models. Together, BAY1436032 is highly effective against all major types of IDH1 mutant AML.